AB0926 Long-Term Safety and Maintenance of Efficacy of Canakinumab Liquid Formulation in Acute Gouty Arthritis Patients: Results From a 36 Week Extension Study. (9th June 2015) - Möricke, R.; Sunkureddi, P.; Toth, E.; Brown, J.P.; Machein, U.; Lheritier, K.; Junge, G.; Kivitz, A.
Abstract : Background: Gouty arthritis (GA) patients who experience frequent flares and have comorbidities have limited treatment options and need effective alternative treatments. Canakinumab (CAN), a selective, human, anti-interleukin-1β monoclonal antibody, has been approved in the European Union for the treatment of difficult-to-treat GA patients. Objectives: A liquid formulation of CAN, presented as pre-filled syringe (CAN-PFS) has been developed to improve upon the lyophilized form (CAN-LYO) that requires reconstitution. A cumulative safety and efficacy results covering a total of 48 weeks are presented. Methods: GA patients completing the 12 week core study 1 were enrolled in a 36 week open label extension (E1) study. All patients entering E1 received CAN-PFS 150 mg sc on demand upon new GA flare irrespective of assigned treatment during randomization [CAN-PFS, CAN-LYO or triamcinolone acetonide 40 mg (TA)]. The primary objective was to confirm the long-term safety of CAN-PFS vs TA. Secondary objectives included evaluation of CAN-PFS vs TA and CAN-LYO vs PFS for the time to first new flare over 48 weeks. Long-term safety outcomes and safety upon re-treatment were assessed as exposure-adjusted incidence rate of adverse events (AEs) and serious AEs (SAEs). Results: Of 397 patients randomized in the core study, 232 (58.4%) entered E1, of which 198 (50%) completed E1. Baseline characteristics were comparable between the treatment groups. The exposure-adjusted incidence of AEs was lower for both CAN-PFS (254.9/100 pyr) and CAN-LYO (224.8/100 pyr) groups when compared with TA (362.7/100 pyr) over the 48 weeks. The exposure-adjusted incidence of SAEs was 14.7/100, 16.1/100, 15.5/100 pyr in patients randomized to CAN-PFS, CAN-LYO and TA groups, respectively. Infections and infestations were the most frequently reported SAE in the CAN-PFS (3.4/100 pyr), CAN-LYO (3.2/100 pyr), TA (0/100 pyr) groups. Over 48 weeks, one death (cardiac failure), not suspected to be related to study drug, was reported in a patient randomized to CAN-PFS who was not re-treated over 48 weeks. Overall, no new safety signals were observed in this extension study. CAN-PFS treatment significantly delayed time to first new flare vs TA patients with a relative risk reduction of 55% (HR, 0.45; 95% CI, 0.32 to 0.64; p<0.0001) over 48 weeks. The mean number of new GA flares per patient was lower for both CAN-LYO (0.50) and CAN-PFS (0.76) groups when compared with the TA group (0.96). Patients in the CAN-PFS group had a 56% reduction in the number of new flares compared to the TA group (rate ratio of 0.44, 95% CI 0.32 to 0.61, p<0.0001). However, both CAN treatments showed a similar mean flare rate per year (CAN-PFS, 0.95; CAN-LYO, 1.13). Conclusions: These results further corroborate the long-term safety and efficacy of canakinumab liquid formulation in patients with frequent GA flares. The safety profile of canakinumab was consistent with the one observed in the core study and the efficacy of canakinumab pre-filled syringe was maintained upon re-treatment. References: Sunkureddi P, et al. Arthritis & Rheumatism 2013;65(10):S498. Disclosure of Interest: R. Möricke: None declared, P. Sunkureddi Grant/research support from: Novartis, E. Toth: None declared, J. Brown Grant/research support from: Abvie, Amgen, Eli Lilly, Novartis, Pfizer, Roche, Takeda, Consultant for: Amgen, Eli Lilly, Speakers bureau: Amgen, Eli Lilly, U. Machein Employee of: Novartis, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, G. Junge Employee of: Novartis, A. Kivitz: None declared